2023
DOI: 10.1037/fam0001091
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ secure base script knowledge predicts observed sensitive caregiving and discipline toward twin children.

Abstract: The present study investigated associations between parents’ secure base script knowledge and parental sensitivity and sensitive discipline in 461 families with 922 same-sex twin children (Mage = 7.00, SD = 2.18). In addition, we explored whether the strength of the associations between parents’ secure base script knowledge and parental sensitivity and sensitive discipline were similar for mono- and dizygotic twin siblings. Parental sensitivity was observed during a computerized version of a structured coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
(142 reference statements)
0
0
0
Order By: Relevance
“…Nevertheless, despite the extensive examination of these studies, the authors concluded that a "transmission gap" persisted of the correspondence between parental attachment representations and child attachment that is not explained by parental sensitivity. Other parental constructs might explain part of this gap, such as parental sensitive discipline, which has been found to be predicted by parental secure base script knowledge (Witte et. al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, despite the extensive examination of these studies, the authors concluded that a "transmission gap" persisted of the correspondence between parental attachment representations and child attachment that is not explained by parental sensitivity. Other parental constructs might explain part of this gap, such as parental sensitive discipline, which has been found to be predicted by parental secure base script knowledge (Witte et. al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In sum, in the current study we examined the intergenerational transmission of attachment model (Van IJzendoorn, 1995;Verhage et al, 2016) using the ASA with both parent and child . We investigated as mediators parental sensitivity, which has consistently been found to play a role in the transmission of attachment, and, additionally, parental sensitive discipline, which we have found to be also predicted by parental secure base script knowledge in an earlier study (Witte et al, 2023) and which might serve to further narrow the transmission gap. Moreover, we investigated the role of child genetic and temperamental differential susceptibility in the intergenerational transmission of attachment.…”
Section: Attachmentmentioning
confidence: 94%
See 2 more Smart Citations